High-toughness and rapid-self-recovery anti-swelling hydrogel and application thereof as strain sensor
By preparing anti-swelling hydrogel with a graded heterostructure, the problems of low mechanical properties and insufficient self-restoration ability of hydrogels in underwater environments are solved, and a hydrogel with high strength and toughness and rapid self-restoration are achieved, suitable for flexibility Application of wearable strain sensors.
Patent Information
- Application Number
- CN202411583876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing anti-swelling hydrogels have low mechanical properties and insufficient self-resilience in underwater environments, making it difficult to meet the needs of flexible wearable strain sensors.
Preparation of the precursor solution by dissolving the polymerizable monomer, multivalent ionic salt and photoinitiator in dimethyl sulfoxide, ultraviolet photopolymerization is performed to form an organic pregel, and the solvent is removed by water soaking to form a π-π stacking with π-π The hydrogel interacts with cation-π-grade heterostructures to enhance its mechanical and swelling resistance.
It significantly improves the strength, toughness and self-restoration ability of the hydrogel, enhances its swelling resistance in the underwater environment, and imparts excellent strain sensing performance, achieving reliable transmission of underwater information.
Smart Images

Figure CN119264320A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of smart gel materials, and in particular relates to a high-toughness and fast self-recovery anti-swelling hydrogel and an application thereof as a strain sensor. Background Art
[0002] Among many flexible sensing materials, conductive hydrogels are particularly attractive for the manufacture of flexible wearable strain sensors due to their unique physicochemical properties, such as good flexibility, conductivity, stretchability, and biocompatibility. Today, strain sensors based on conductive hydrogels have been widely used in a variety of fields such as flexible robots and medical diagnosis. Significant progress has been made in the development of hydrogel strain sensors for terrestrial applications, but their application in underwater environments still faces great challenges, mainly due to the inherent swelling behavior of hydrogels in aqueous environments. This swelling behavior damages the original structure of the hydrogel network, resulting in degradation of its mechanical properties and reduced sensing reliability.
[0003] In recent years, initial progress has been made in the design of anti-swelling hydrogel sensors for underwater environments. However, current anti-swelling hydrogel sensors still exhibit low mechanical strength, usually only in the kilopascal range. In addition, some anti-swelling hydrogel sensors exhibit incomplete self-recovery ability after deformation, or the self-recovery process takes a long time. Summary of the invention
[0004] In view of this, one of the objects of the present invention is to provide a high-toughness and fast self-recovery anti-swelling hydrogel. Another object of the present invention is to provide a method for preparing the above-mentioned high-toughness and fast self-recovery anti-swelling hydrogel. Another object of the present invention is to provide a method for preparing a high-toughness and fast self-recovery anti-swelling hydrogel strain sensor and its application.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides an anti-swelling hydrogel, wherein the hydrogel is prepared by a method comprising the following steps:
[0007] S1, dissolving a polymerizable monomer, a multivalent ion salt and a photoinitiator in dimethyl sulfoxide to prepare a precursor solution; the polymerizable monomer includes a carboxyl-containing polymerizable monomer and a phenyl (oxy) group (i.e., phenyl or phenoxy)-containing acrylate monomer;
[0008] S2, the precursor solution is subjected to ultraviolet polymerization under an inert atmosphere (such as nitrogen gas is passed to remove oxygen) to obtain an organic pre-gel;
[0009] S3, soaking the organic pre-gel in water, and removing the solvent in the gel by solvent exchange to obtain the hydrogel.
[0010] The hydrogel of the invention uses polymerizable monomers (including polymerizable monomers containing carboxyl groups and acrylate monomers containing benzene (oxy) groups), multivalent ion salts, photoinitiators and organic solvent dimethyl sulfoxide (DMSO) as raw materials.
[0011] In some embodiments, the ratio of the polymerizable monomer to dimethyl sulfoxide is: 0.03-0.07 mol: 6-10 g.
[0012] In some embodiments, the carboxyl group-containing polymerizable monomer accounts for 60% to 90% of the total molar amount of the polymerizable monomer.
[0013] In some embodiments, the acrylate monomer containing a phenyl(oxy) group accounts for 10% to 40% of the total molar amount of the polymerizable monomers.
[0014] In some embodiments, the multivalent ion salt accounts for 0.2% to 2% of the total molar amount of the polymerizable monomers.
[0015] In some embodiments, the photoinitiator comprises 0.1% to 1% of the total molar amount of the polymerizable monomers.
[0016] In some embodiments, the carboxyl-containing polymerizable monomer includes at least one of acrylic acid, methacrylic acid, and maleic acid.
[0017] In some embodiments, the acrylate monomer containing a phenyl(oxy) group includes at least one of phenoxyethyl methacrylate and benzyl acrylate. Phenyl or phenoxy is a prerequisite for π-π stacking and cation-π interaction in the reaction mechanism of the present invention.
[0018] In some embodiments, the multivalent ion salt includes at least one of ferric chloride, aluminum chloride hexahydrate, and zirconium oxychloride octahydrate. The role of introducing high-valent metal salts in the system of the present invention is mainly to: 1. enhance the mechanical properties of the hydrogel; 2. improve the anti-swelling property of the hydrogel; 3. give the hydrogel conductive and sensing properties.
[0019] In some embodiments, the photoinitiator includes at least one of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0020] In some embodiments, the organic solvent is dimethyl sulfoxide.
[0021] In some embodiments, in step S2, the ultraviolet light polymerization time is 5 to 50 minutes, and the ultraviolet light wavelength is 365 nm or 405 nm. In some specific implementation examples, the polymerization reaction is carried out under the irradiation of an ultraviolet lamp; the power of the ultraviolet lamp is 8 to 30 watts.
[0022] In some embodiments, in step S2, the precursor solution is transferred to a mold before UV polymerization. In some specific implementation examples, the precursor solution is passed through nitrogen for 3-10 minutes to remove oxygen, and then transferred to a cylindrical mold. The cylindrical mold has a height of 5-15 cm and a bottom diameter of 2-5 mm.
[0023] In some embodiments, in step S3, water is replaced every 10-16 hours. The water replacement lasts for 3 to 7 days. The present invention requires that during the water immersion process, on the one hand, the solvent is removed to achieve π-π stacking and cation-π interaction formation in the hydrophobic region; on the other hand, the original monodentate, bidentate or (tridentate) carboxyl-metal ion coordination complex is reorganized to form more tridentate (tetradentate) carboxyl-metal ion coordination complexes. Different metal ions Fe 3+ 、Al 3+ or Zr 4 + Corresponding to different numbers of teeth for coordination and chelation.
[0024] In a second aspect, the present invention provides an application of an anti-swelling hydrogel in preparing a hydrogel strain sensor. For example, the hydrogel strain sensor can be fixed on a finger and then transmit information underwater through Morse code.
[0025] In a third aspect, the present invention provides a hydrogel strain sensor, wherein a long strip of aluminum foil is encapsulated between two insulating tapes to prepare a wire, and the two ends of the anti-swelling hydrogel are encapsulated with the wire and auxiliary sealed with insulating tape; that is, the hydrogel strain sensor is prepared.
[0026] In a fourth aspect, the present invention provides an application of a hydrogel strain sensor in an underwater environment.
[0027] In some embodiments, the hydrogel strain sensor is fixed to a finger and then transmits information underwater through Morse code. In some specific implementation examples, a method for preparing a high-toughness and fast self-recovery anti-swelling hydrogel strain sensor and its application are provided:
[0028] (1) Wrapping a long strip of aluminum foil between two insulating tapes to prepare a wire;
[0029] (2) encapsulating both ends of the anti-swelling hydrogel with wires and sealing with insulating tape to prepare a hydrogel sensor;
[0030] (3) The anti-swelling hydrogel sensor is fixed to the finger and then transmits information underwater through Morse code.
[0031] The reaction mechanism of the present invention is as follows:
[0032] In the organic pregel, the polymer segments containing carboxyl groups and benzene rings are kept in a dispersed state, which hinders the formation of intermolecular interactions. At the same time, dimethyl sulfoxide (DMSO) stabilizes the dissociated state of metal ions through the solvation effect, inhibiting their tendency to form metal coordination bonds and cation-π interactions with the carboxyl groups and benzene rings in the segments, respectively. Although the organic pregel was successfully prepared, the presence of DMSO caused it to lack effective energy dissipation capacity inside, resulting in extremely poor mechanical properties. Subsequently, the organic pregel was incubated in a large amount of water, and the soaking water was repeatedly replaced to remove the DMSO inside the gel. During the water incubation process, due to the difference in affinity of the polymer segments containing carboxyl groups and benzene rings to water, phase separation was induced inside the gel, causing the transparent organic pregel to gradually transform into an opaque hydrogel. Among them, the polymer segments containing benzene rings, due to their low affinity to water, aggregated to form a region rich in hydrophobic units dominated by π-π stacking and cation-π interactions. At the same time, as the DMSO and excess metal ions in the gel are gradually removed, strong multi-dentate COO bonds are formed between the carboxyl-containing polymer chains. - -M n+ Metal coordination bonds. Through the water-induced incubation strategy, COO - -M n+ The metal coordination bonds act as the 'rigid' regions, and the PEA-rich domains with π-π stacking and cation-π interactions act as the 'flexible' regions in the hierarchical heterostructure.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The rigid-flexible hierarchical heterogeneous structure in the hydrogel is conducive to π-π stacking, cation-π interaction and COO in the hydrogel network. - -M n+ Under the action of external force, the metal coordination bonds gradually break from weak to strong, effectively dissipating energy, thereby significantly enhancing the strength and toughness of the hydrogel.
[0035] (2) Rigid and strong COO - -M n+ The metal coordination bonds ensure the stability of the hydrogel network skeleton, while the flexible and easily recoverable π-π stacking and cation-π interactions effectively dissipate energy and promote rapid reconstruction of the structure. The synergistic effect of this hierarchical dynamic cross-linking enables the hydrogel to exhibit excellent self-healing ability.
[0036] (3) The introduction of multiple dynamic interactions effectively increased the cross-linking density of the hydrogel network and significantly enhanced the elastic retraction force of the hydrogel, thereby giving the hydrogel excellent anti-swelling ability.
[0037] (4) Free ions (Cl- and Mn+ ) gives it strain sensing properties.
[0038] (5) Hydrogels that combine excellent mechanical properties, strain sensing properties, and anti-swelling properties are assembled into underwater strain sensors, which realize underwater information transmission through Morse code. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0040] Figure 1 (a) and (b) are P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ (DMSO) organic pregel, P(AA-PEA)-Zr 4+ Infrared spectra of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1.
[0041] Figure 2 (a), (b) and (c) are P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ Tensile stress-strain curves of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1, as well as the corresponding toughness and elastic modulus values.
[0042] Figure 3 (a) and (b) are P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ Anti-swelling properties of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1.
[0043] Figure 4 (a), (b) and (c) are P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ Self-recovery properties of hydrogels and the corresponding stress and dissipated energy recovery rates.
[0044] Figure 5 (a), (b), (c) and (d) are P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ Sensitivity factor, frequency responsiveness, and relative resistance change of hydrogel under different strains.
[0045] Figure 6 P(AA-PEA)-Zr prepared in Example 1 of the present invention 4+ Application of hydrogel sensors in underwater information transmission; wherein (a) is the definition of Morse code; (b), (c) and (d) are P(AA-PEA)-Zr prepared in Example 1 4+Schematic diagram of underwater sensing applications of hydrogels, underwater finger bending signals, definitions of “·” and “-”, and transmission of “SOS” information. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0047] Based on the information contained in this application, it is easy for those skilled in the art to make various changes to the precise description of the present invention without departing from the spirit and scope of the appended claims. It should be understood that the scope of the present invention is not limited to the defined process, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention. In fact, various changes that the technicians in this field or related fields can obviously make to the embodiments of the present invention are all covered within the scope of the appended claims.
[0048] Example 1
[0049] The method for preparing a high-toughness and fast self-recovery anti-swelling hydrogel of this embodiment comprises the following steps:
[0050] (1) 3.06 g of acrylic acid (AA), 1.44 g of phenoxyethyl methacrylate (PEA), 31.6 mg of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, and 241.5 mg of zirconium oxychloride octahydrate were dissolved in 8.0 g of dimethyl sulfoxide (DMSO) to prepare a uniform precursor solution.
[0051] (2) The precursor solution was passed through nitrogen for 5 minutes to remove oxygen, and then transferred to a cylindrical mold and polymerized under ultraviolet light for 20 minutes to obtain P(AA-PEA)-Zr 4+ (DMSO) organic pregel; wherein: the cylindrical mold is 8 cm high and the bottom diameter is 4 mm; the wavelength of the ultraviolet lamp is 405 nm and the power is 25 watts.
[0052] (3) The organic pregel was immersed in a large amount of water to remove DMSO, and the water was changed every 12 hours for 4 days to finally obtain P(AA-PEA)-Zr 4+ Hydrogel.
[0053] Example 2
[0054] The method for preparing a high-toughness and fast self-recovery anti-swelling hydrogel of this embodiment comprises the following steps:
[0055] (1) 3.66 g of methacrylic acid (MAA), 1.215 g of benzyl acrylate (BnA), 31.6 mg of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, and 241.5 mg of zirconium oxychloride octahydrate were dissolved in 8.0 g of dimethyl sulfoxide (DMSO) to prepare a uniform precursor solution.
[0056] (2) The precursor solution was passed through nitrogen for 5 minutes to remove oxygen, and then transferred to a cylindrical mold and polymerized under ultraviolet light for 15 minutes to obtain P(MAA-BnA)-Zr 4+ (DMSO) organic pregel; wherein: the cylindrical mold is 8 cm high and the bottom diameter is 4 mm; the wavelength of the ultraviolet lamp is 405 nm and the power is 25 watts.
[0057] (3) The organic pregel was soaked in a large amount of water to remove DMSO, and the water was changed every 12 hours for 4 days to finally obtain P(MAA-BnA)-Zr 4+ Anti-swelling hydrogel.
[0058] Example 3
[0059] The method for preparing a high-toughness and fast self-recovery anti-swelling hydrogel of this embodiment comprises the following steps:
[0060] (1) 3.06 g of acrylic acid (AA), 1.44 g of phenoxyethyl methacrylate (PEA), 31.6 mg of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, and 180.75 mg of aluminum chloride hexahydrate were dissolved in 8.0 g of dimethyl sulfoxide (DMSO) to prepare a uniform precursor solution.
[0061] (2) The precursor solution was passed through nitrogen for 5 minutes to remove oxygen, and then transferred to a mold and polymerized under ultraviolet light for 20 minutes to obtain P(AA-PEA)-Al 3+ (DMSO) organic pregel; wherein: the cylindrical mold is 8 cm high and the bottom diameter is 4 mm; the wavelength of the ultraviolet lamp is 405 nm and the power is 25 watts.
[0062] (3) The organic pregel was immersed in a large amount of water to remove DMSO, and the water was changed every 12 hours for 4 days to finally obtain P(AA-PEA)-Al 3+ Anti-swelling hydrogel.
[0063] Comparative Example 1
[0064] A method for preparing a hydrogel in this comparative example comprises the following steps:
[0065] (1) 3.06 g of acrylic acid (AA), 1.44 g of phenoxyethyl methacrylate (PEA), and 31.6 mg of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester were dissolved in 8.0 g of dimethyl sulfoxide (DMSO) to prepare a uniform precursor solution.
[0066] (2) The precursor solution was passed through nitrogen for 5 minutes to remove oxygen, and then transferred to a mold and polymerized under ultraviolet light for 20 minutes to obtain P(AA-PEA)(DMSO) organic pregel; wherein: the cylindrical mold was 8 cm high and had a bottom diameter of 4 mm; the ultraviolet light had a wavelength of 405 nm and a power of 25 watts.
[0067] (3) The organic pregel was soaked in a large amount of water to remove DMSO, and the water was replaced every 12 hours for 4 days to finally obtain P(AA-PEA) hydrogel.
[0068] Performance Testing
[0069] (I) Infrared test of different gels
[0070] The P(AA-PEA)-Zr prepared in Example 1 of the present invention was investigated. 4+ (DMSO) organic pregel, P(AA-PEA)-Zr 4+ ATR-FTIR spectra of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1. Figure 1 As shown in a, in P(AA-PEA)-Zr 4+ In the spectrum of (DMSO) organic pregel, 1011 cm -1 and 949cm -1 The two characteristic peaks correspond to the S=O groups in DMSO. 4+ The obvious disappearance in the spectrum of the hydrogel confirmed that DMSO had been completely expelled from the hydrogel. Figure 1 b shows the P(AA-PEA) and P(AA-PEA)-Zr 4+ Comparison of ATR-FTIR spectra of hydrogels. The characteristic peak of aromatic ring skeleton vibration (C=C) is from 1600 cm -1 Move to 1598cm -1 , indicating the formation of π-π stacking and cation-π interactions. These interactions lead to the redistribution and delocalization of the electron cloud of the aromatic ring, thereby weakening the C=C bond and causing the red shift of the characteristic peak. At the same time, COO - The symmetric stretching vibration of the group is from 1407cm -1 Move to 1413cm -1 , proving that COO -The blue shift phenomenon is due to the formation of the coordination bond that enhances the COO - The force constant of the CO bond in the group increases, thereby increasing the vibration frequency.
[0071] (II) Tensile test of different hydrogels
[0072] The tensile test was performed to investigate the P(AA-PEA)-Zr prepared in Example 1 of the present invention. 4+ The mechanical properties of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1. Figure 2 As shown in a, 2b and 2c, the mechanical properties of P(AA-PEA) hydrogel are poor, with a breaking strength of 0.13 MPa and a toughness of 0.40 MJ / m 3 , Young's modulus is 0.019MPa. In contrast, P(AA-PEA)-Zr 4+ The hydrogel exhibited even better mechanical properties, with a fracture strength of 1.42 MPa and a toughness of 1.98 MJ / m 3 , and Young’s modulus reached 0.26MPa, which were 10.92, 4.95, and 13.68 times the corresponding performances of P(AA-PEA) hydrogel, respectively. 4+ The rigid-flexible hierarchical heterostructure in the hydrogel is conducive to π-π stacking, cation-π interaction and COO - -M n+ Under the action of external force, the metal coordination bonds gradually break from weak to strong, effectively dissipating energy, thereby significantly enhancing the strength and toughness of the hydrogel.
[0073] (III) Anti-swelling performance test of different hydrogels
[0074] The P(AA-PEA)-Zr prepared in Example 1 of the present invention was further investigated. 4+ Anti-swelling properties of the hydrogel and the P(AA-PEA) hydrogel prepared in Comparative Example 1. Figure 3 a and 3b show P(AA-PEA) and P(AA-PEA)-Zr 4+ Swelling process and swelling kinetics of hydrogels in water environment. After immersion in water for 15 days, P(AA-PEA) hydrogels swelled and deformed significantly, while P(AA-PEA)-Zr 4+ The hydrogel still maintains its original morphology. Meanwhile, the swelling rate of P(AA-PEA) hydrogel is as high as 29.6%, while that of P(AA-PEA)-Zr 4+The swelling rate of the hydrogel is only -2.49%. The swelling capacity of the hydrogel depends on the balance between the swelling force and the elastic retraction force. Increasing the network crosslinking density of the hydrogel can strengthen its elastic retraction force, thereby inhibiting its swelling behavior. In the new water environment, the hydrogel will inevitably be affected by the new swelling force. Due to the low crosslinking density of the P(AA-PEA) hydrogel, its elastic retraction force is not enough to resist the swelling force, resulting in a significant increase in the swelling rate. However, P(AA-PEA)-Zr 4+ π-π stacking, cation-π interactions, and COO in hydrogels - -M n+ The metal coordination bonds synergistically form a highly dense cross-linked network, which greatly enhances the elastic retraction force of the hydrogel, thereby significantly improving its anti-swelling properties.
[0075] (IV) P(AA-PEA)-Zr 4+ Rapid self-healing properties of hydrogels
[0076] The preparation of P(AA-PEA)-Zr in Example 1 of the present invention was further investigated. 4+ The self-healing properties of hydrogels. Figure 4 As shown in (a), compared with the first loading-unloading curve, the area of the second loading-unloading curve is significantly reduced without recovery time, but the area gradually increases with the extension of recovery time. Figure 4 b and Figure 4 c shows the recovery rate of stress and dissipated energy, respectively. 4+ The hydrogel only has 93.13% stress recovery (180.82 kPa) and 62.16% dissipated energy recovery (11.21 kJ / m 3 After only two minutes of standing, the stress recovery of the hydrogel reached 100.1% (194.40 kPa) and the dissipated energy recovered to 96.52% (17.41 kJ / m 3 ); after three minutes of recovery, the stress (100.7%, 195.66 kPa) and dissipated energy (100.1%, 18.06 kJ / m 3 ) are fully recovered. The above results indicate that the rigid and strong metal coordination bonds ensure the stability of the network skeleton, while the flexible and easily recoverable π-π stacking and cation-π interactions effectively dissipate energy and promote the rapid reconstruction of the structure. This synergistic effect of hierarchical dynamic crosslinking makes P(AA-PEA)-Zr 4+ The hydrogel exhibited excellent self-healing ability.
[0077] (V) P(AA-PEA)-Zr 4+ Strain sensing properties of hydrogels
[0078] The preparation of P(AA-PEA)-Zr in Example 1 of the present invention was further investigated. 4+ Strain sensing properties of hydrogels. Figure 5 a shows two nearly linear intervals, each with a different slope, and the corresponding sensitivity coefficient is 1.86 in the 0-50% strain range and 2.42 in the 50-200% strain range, demonstrating the excellent sensitivity of the hydrogel sensor. Figure 5 As shown in b, P(AA-PEA)-Zr 4+ The hydrogel sensor exhibits good frequency responsiveness, ensuring its robust real-time monitoring capability. Under a 25% cyclic strain, the hydrogel sensor can reliably and accurately monitor frequency changes from 0.1 to 0.25 Hz. Figure 5 As shown in Figures 5c and 5d, stable real-time relative resistance change (ΔR / R0) signals were observed under both high strain (25%, 50%, 75% and 100%) and low strain (3%, 6%, 9% and 12%). Each step-wise strain change will cause a corresponding signal change. For different strain conditions, the signal characteristics are significantly different, demonstrating the excellent sensitivity and accuracy of the sensor.
[0079] (VI) P(AA-PEA)-Zr 4+ Hydrogel sensors for underwater information transmission
[0080] Preparation of P(AA-PEA)-Zr based on Example 1 of the present invention 4+ The excellent mechanical properties, sensing performance and anti-swelling properties of the hydrogel further investigated its use as a strain sensor to transmit Morse code-based information in underwater environments. Figure 6 As shown in a, the Morse code is composed of the symbols '·' and '—', and different arrangements and combinations of these symbols can represent various letters. Figure 6 b shows that an underwater sensing device was assembled to record the real-time resistance signal. Figure 6 c shows the P(AA-PEA)-Zr 4+ The hydrogel sensor was fixed on the finger to monitor the long-term and short-term finger bending motion in the underwater environment, and the corresponding long-term and short-term ΔR / R0 signals were accurately detected. Based on this, an underwater communication mechanism based on Morse code was established, in which the instantaneous resistance change represents '·' and the long-term resistance signal represents '—'. Therefore, Figure 6 As shown in (d), by adjusting the bending deformation duration of the hydrogel sensor on the finger, effective information consisting of different letters such as "SOS" can be transmitted in an underwater environment.
[0081] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. An anti-swelling hydrogel, characterized in that: The hydrogel is prepared by a method comprising the following steps: S1, dissolving a polymerizable monomer, a multivalent ion salt and a photoinitiator in dimethyl sulfoxide to prepare a precursor solution; the polymerizable monomer comprises a carboxyl-containing polymerizable monomer and a phenyl or phenoxy-containing acrylate monomer; S2, the precursor solution is ultraviolet-polymerized under an inert atmosphere to obtain an organic pre-gel; S3, soaking the organic pre-gel in water, and removing the solvent in the gel by solvent exchange to obtain the hydrogel.
2. The anti-swelling hydrogel according to claim 1, characterized in that Include at least one of the following technical features: A1, the usage ratio of the polymerizable monomer to dimethyl sulfoxide is: 0.03-0.07 mol: 6-10 g; A2, the amount of the carboxyl-containing polymerizable monomer accounts for 60% to 90% of the total molar amount of the polymerizable monomer; A3, the amount of the acrylate monomer containing phenyl or phenoxy group accounts for 10% to 40% of the total molar amount of the polymerizable monomers; A4, the amount of the multivalent ion salt is 0.2% to 2% of the total molar amount of the polymerizable monomers; A5. The amount of the photoinitiator used is 0.1% to 1% of the total molar amount of the polymerizable monomers.
3. The anti-swelling hydrogel according to claim 1 or 2, characterized in that: Include at least one of the following technical features: B1, the carboxyl-containing polymerizable monomer includes at least one of acrylic acid, methacrylic acid, and maleic acid; B2, the phenyl or phenoxy-containing acrylate monomer includes at least one of phenoxyethyl methacrylate and benzyl acrylate; B3, the multivalent ion salt includes at least one of ferric chloride, aluminum chloride hexahydrate, and zirconium oxychloride octahydrate; B4. The photoinitiator includes at least one of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
4. The anti-swelling hydrogel according to claim 1, characterized in that In step S2, the ultraviolet light polymerization time is 5 to 50 minutes, and the ultraviolet light wavelength is 365 nm or 405 nm.
5. The anti-swelling hydrogel according to claim 1, characterized in that In step S2, the precursor solution is transferred to a mold before UV polymerization.
6. The anti-swelling hydrogel according to claim 1, characterized in that In step S3, the water is replaced every 10-16 hours; the water replacement lasts for 3 to 7 days.
7. Use of the anti-swelling hydrogel according to any one of claims 1 to 6 in preparing a hydrogel strain sensor.
8. A hydrogel strain sensor, characterized in that: A long strip of aluminum foil is encapsulated between two insulating tapes to prepare a wire, and the two ends of the anti-swelling hydrogel according to any one of claims 1 to 6 are encapsulated with the wire and sealed with insulating tape to prepare the hydrogel strain sensor.
9. Use of the hydrogel strain sensor according to claim 8 in an underwater environment.
10. The use according to claim 9, characterized in that: The hydrogel strain sensor is fixed to a finger and then transmits information underwater through Morse code.
Citation Information
Patent Citations
Aqueous dispersion of gel particles, method for producing same, and image formation method
CN107406532A
Method for enhancing polyelectrolyte hydrogel through metal ion in-situ coordination
CN113480755A
Anti-swelling gel as well as preparation method and application thereof
CN118206686A
Process for producing transparent GELS with mechanical and sorption properties
GB1405056A
Water-based gel-inclusive resin particle emulsion and method for producing the water-based gel-inclusive resin particle emulsion
JP5971665B1
Cited By
Stimuli-responsive self-repairing fluorescent hydrogel as well as preparation method and anti-counterfeiting application thereof
CN120757697A
Stimuli-responsive self-healing fluorescent hydrogel, preparation method thereof and anti-counterfeiting application thereof
CN120757697B